Sol - Gel synthesis and characterization of magnesium peroxide nanoparticles - Chan, Yen (IOP Publishing Ltd, 2014)
Magnesium peroxide is an excellent source of oxygen in agriculture applications, for instance it is used in waste management as a material for soil bioremediation to remove contaminants from polluted underground water, biological wastes treatment to break down hydrocarbon, etc. In the present study, sol-gel synthesis of magnesium peroxide (MgO2) nanoparticles is reported. Magnesium peroxide is odourless; fine peroxide which releases oxygen when reacts with water. During the sol-gel synthesis, the magnesium malonate intermediate is formed which was then calcinated to obtain MgO2 nanoparticles. The synthesized nanoparticles were characterized using Thermo gravimetric -Differential Thermal Analysis (TG- DTA), X-Ray Diffraction studies (XRD) and High Resolution Transmission Electron Microscope (HRTEM). Our study provides a clear insight that the formation of magnesium malonate during the synthesis was due to the reaction between magnesium acetate, oxalic acid and ethanol. In our study, we can conclude that the calcination temperature has a strong influence on particle size, morphology, monodispersity and the chemistry of the particles.